2014
DOI: 10.1371/journal.pone.0110140
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Limb Shortening following Stroke: What’s in a Name?

Abstract: BackgroundDifficulty advancing the paretic limb during the swing phase of gait is a prominent manifestation of walking dysfunction following stroke. This clinically observable sign, frequently referred to as ‘foot drop’, ostensibly results from dorsiflexor weakness.ObjectiveHere we investigated the extent to which hip, knee, and ankle motions contribute to impaired paretic limb advancement. We hypothesized that neither: 1) minimal toe clearance and maximal limb shortening during swing nor, 2) the pattern of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 39 publications
3
29
1
Order By: Relevance
“…However, the causal relations between these compensations and reduced foot clearance have never been established. Stroke patients exhibit similar or higher foot clearance values compared to healthy individuals (Little, McGuirk, & Patten, 2014; Matsuda et al, 2017) suggesting one or more of these aforementioned compensations could be redundant. It is a commonly held belief that hip abduction, the main frontal plane component of hip circumduction, compensates for lack of knee flexion (Perry & Burnfield, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, the causal relations between these compensations and reduced foot clearance have never been established. Stroke patients exhibit similar or higher foot clearance values compared to healthy individuals (Little, McGuirk, & Patten, 2014; Matsuda et al, 2017) suggesting one or more of these aforementioned compensations could be redundant. It is a commonly held belief that hip abduction, the main frontal plane component of hip circumduction, compensates for lack of knee flexion (Perry & Burnfield, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…(Leiper and Craik 1991) Influence values, as used here, represent more than the magnitude of joint excursion. Influence represents the relational contribution of the joint excursion to the functional tasks of limb clearance and limb shortening (Little, McGuirk, and Patten 2014), that is the concurrent coordination between joints to achieve a task goal. Furthermore, influence quantifies the respective joint contributions that are temporally linked to their task goal throughout the gait cycle.…”
Section: Is Slow Walking a Different Behavior?mentioning
confidence: 99%
“…Gait researchers commonly speed-match, using healthy individuals walking at very slow speeds, for a direct comparison with pathologic gait. (Lehmann et al 1987;Chen et al 2005;Little, McGuirk, and Patten 2014) However, it has been suggested that very slow walking (<0.4-0.5 m/sec) may be a unique motor behavior utilizing a different control strategy than walking at comfortable walking speeds. (Leiper and Craik 1991;Smith and Lemaire 2018) If this were the case, speed-matching for biomechanical studies may not always be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…A2 is typically diminished following stroke; the extent to which A2 is decreased is strongly associated with walking speed, capacity for gait speed modulation, and severity of walking dysfunction (Winter 1983; Olney et al 1991; Jonkers et al 2009; Kitatani et al 2016). Propulsive power generated by the plantarflexors also drives knee flexion during swing, one of the major contributors to limb clearance (Nadeau et al 1999; Little et al 2014). For all that is known about the biomechanical deficits following stroke, much less is known about the specific neural mechanisms underlying these impairments.…”
Section: Introductionmentioning
confidence: 99%